Gender Inequalities in Tech-driven Research and Innovation Living the Contradiction - Griffin, Gabriele (Bristol University Press, 2022)
ePDF and ePUB available Open Access under CC-BY-NC-ND licence. This volume explores why, despite numerous programmes, women continue to constitute a minority in tech-driven research and innovation areas in the Nordic countries. Putting the spotlight on the lived experience of women, the authors make an invaluable contribution to global debates around the mechanisms that maintain gendered structures in Research and Innovation, from academia to biotechnology and IT.